Foreign Aids and Nigeria’s National Development: A Study of the Fourth Republic - Johnbull Onoriode; Ayegbunam Francis Ikenga (Pinisi Journal of Social Science, 2025)
Foreign aid has remained a crucial component of international development cooperation, especially for developing countries like Nigeria. Since the return to democratic governance in 1999 (the Fourth Republic), Nigeria has witnessed a steady inflow of foreign assistance to address developmental challenges and support socio-economic growth. This study examined the effects of foreign aid on national development in Nigeria during the Fourth Republic, focusing on sectors such as health, education, and infrastructure. With a growing inflow of foreign assistance since 1999, especially following the Paris Club debt relief in 2005, Nigeria has received substantial aid from bilateral and multilateral donors. This study used a historical research design, with content analysis applied for data evaluation. It focuses on thoroughly reviewing documented information, from which relevant materials were extracted for analysis. The study was anchored on the Dependency Theory, which argues that foreign aid, while beneficial, can perpetuate dependency if not managed properly. It further explores the role of institutional capacity, governance, and corruption in determining the success of aid projects. The data collected for this study were synthesized and analyzed using trend analysis techniques. The findings reveal that foreign aid has contributed positively to Nigeria’s health, education, and infrastructure sectors. However, systemic challenges, including weak governance, corruption, and poor coordination among stakeholders, have undermined the effectiveness of aid. The study concluded that despite the potential of foreign aid to stimulate national development, its impact is often hindered by governance deficiencies and institutional inefficiencies. Finally, this study recommended, among others, that the government should strengthen institutional capacity and governance by prioritizing training, capacity-building initiatives, and the creation of clear accountability structures to ensure effective utilization of foreign assistance.